Antioxidant and Antiaging Assays of Ageratum conyzoides (L.) Ethanolic Extract - Sutjiatmo, Afifah B; Edriayani, Novi; Mulyasari, Tira Endang; Hermanto, Faizal; Fahrauk, M.; Sukandar, Elin Y.; Kusuma, Hanna Sari Widya; Rizal, Rizal; Widowati, Wahyu (Pharmaceutical Sciences and Research, 2020)
The declining ability of tissues to repair or replace themselves and maintain their structure and normal function is called aging. Aging is caused by free radical that can induce the activation of elastase and collagenase. Ageratum conyzoides (L.) or known as Babadotan is a medicinal plant that has been reported to be a good source of antioxidants that also inhibit aging process. The purpose of this research is to evaluate the antioxidant and antiaging properties of Babadotan Ethanolic Extract (BEE). Franswoth method was used to determine the phytochemical assay of BEE. Measurement of 2,2-diphenyl 1-picrylhydrazyl (DPPH) scavenger was used for antioxidant assay, and inhibitory of elastase and collagenase activities was used for antiaging assay. The analysis of phytochemical compounds exhibited the presence of flavonoids, alkaloids, tannins, polyphenols, steroids and triterpenoids, monoterpenoids and terpenoids, and the absence of saponin. BEE has lower activity on DPPH scavenging activity (IC50 = 80.7 µg/mL) than quercetin (IC50 = 3.25 µg/mL). BEE exhibited lower elastase and collagenase inhibitory activity (IC50 = 45.35 ± 2.2 µg/mL and 55.07 ± 1.1 µg/mL, respectively) compared to quercetin (IC50 = 11.64 ± 0.67 µg/mL and 19.91 ± 0.46 µg/mL). Overall, BEE possesses antioxidant and antiaging activities, although the activities are lower than quercetin.